Effects of drought legacy and tree species admixing on bacterial growth and respiration in a young forest soil upon drying and rewetting. (December 2018) - Rahman, Md Masudur; Hicks, Lettice C.; Verheyen, Kris; Rousk, Johannes; Carnol, Monique
Abstract: In the context of future climate change, the flush of CO2 emissions from soils after drying-rewetting events could have a strong impact on the terrestrial carbon balance. Mixed forests may be more resistant and resilient to drought events compared to monocultures, and as such may modulate the effects of drought on soil functioning belowground. We investigated the influence of mixed planting and drought legacy on respiration and bacterial growth rates ( 3 H Leucine incorporation) in response to drying-rewetting. Soils were sampled from a 7-year old tree diversity experiment (FORBIO), where oak ( Quercus robur L.) trees admixed with one or three other tree species were subjected to ∼50% precipitation reduction for 2 years ("drought legacy"). Respiration increased immediately after rewetting, whereas bacterial growth only started after a distinct lag phase of ca. 7 h. A legacy of drought reduced bacterial growth and respiration rates upon rewetting, however tree species admixing did not modulate the drought legacy effect. Our results suggest that prolonged decrease in precipitation may lead to a reduced CO2 pulse upon drying-rewetting and admixing up to three tree species with oak in a young afforestation would not alleviate drought legacy effects on bacterial growth and respiration rates. Highlights: We investigated drought legacy and tree admixing effects on bacterial growth and respiration rates upon drying-rewetting. Upon rewetting, bacteria exhibited a delayed growth response ('type 2') in all soils. Drought legacy reduced bacterial growth and respiration upon drying-rewetting. Tree species admixing to oak did not modulate the drought legacy effect.